The Luwians of western Anatolia: their neighbours and predecessors - Woudhuizen, Fred (Archaeopress Publishing Ltd, 2018)
A study focusing on the Luwians of Western Anatolia, the geography of their habitat, and their neighbours and predecessors in the region. A reconstruction of western Luwian history and a sketch of their language is presented, based on linguistic data taken from hieroglyphic inscriptions and cuneiform script